Development of Environmentally Appropriate Technology Through Creativity Cooking Oil into Aromateraphy Candles in Dupak Magersari Surabaya - Falasifah, Nihlatul; Azlya Syahrazad, Sharla Nabighah; Umamah, Rosifatul (LP2M INSURI Ponorogo, 2024)
The utilization of used cooking oil into aromatheraphy candles is an effort to develop the creativity of residents to reduce liquid waste pollution in the surrounding environment. Due to the large amount of used cooking oil produced by daily home activities in Dupakmagersari, there is a wonderful chance to manage waste more effectively by turning it into aromatherapy candles. The residents can use this innovation as a creative enterprise since they can sell the products to make money. The purpose of this research is a way to minimize waste oil pollution that can threaten environmental damage and human health. This research uses methods from the problem solving, determination, manufacture, and distribution stages. So that the results of this research, the Dupak Magersari community, Jepara Village, Bubutan Subdistrict, Surabaya City, especially Srikandi Kapirel squad can have the skills to utilize waste oil into goods that have selling value, namely aromatheraphy candles. The community will benefit from the ability to produce and market aromatherapy candles made from used cooking oil, which will increase revenue.